The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1099/jmm.0.000713
|View full text |Cite
|
Sign up to set email alerts
|

Human respiratory syncytial virus: prevalence, viral co-infections and risk factors for lower respiratory tract infections in children under 5 years of age at a general hospital in the Democratic Republic of Congo

Abstract: The prevalence of HRSV is high among children visiting the PGHB for ARI. HRSV infection and lower age are independently associated with the risk of ARI being diagnosed as LRTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Newborns are highly vulnerable to pathogens due to their functional immunological differences from adults as a result of living in a semi-allogeneic sterile environment, where exposure to microbial antigens is limited (3)(4)(5)(6). For example, microorganisms such as respiratory syncytial virus (RSV) cause no or mild disease in adults but induce acute bronchiolitis, viral pneumoniae, and croup in infants, with those between 2 and 6 months of age at the highest risk, especially in low-income countries (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Newborns are highly vulnerable to pathogens due to their functional immunological differences from adults as a result of living in a semi-allogeneic sterile environment, where exposure to microbial antigens is limited (3)(4)(5)(6). For example, microorganisms such as respiratory syncytial virus (RSV) cause no or mild disease in adults but induce acute bronchiolitis, viral pneumoniae, and croup in infants, with those between 2 and 6 months of age at the highest risk, especially in low-income countries (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…This nding goes hand in hand with other literatures and studies done to nd if there was an association between acute respiratory infection and RSV presence [27,20,28]. However, in a study on the prevalence of acute respiratory infection caused by RSV, ndings showed that there was an independent association between RSV and the risk of developing an acute respiratory infection, but this speci c study only included children younger than the age of 5 years old, had a larger number of study sample and was done on a shorter period of time (5 months), those differences could have favoured the difference in ndings from that study and this study on RSV in Kinshasa [29].…”
Section: Discussionmentioning
confidence: 70%
“…Only one study provided a prevalence between 41 and 50% [ 1 ]. Finally, three studies provided a prevalence between 51% and 57.5% and were among hospitalised samples [ 13 , 46 ]. Compared to studies that used community samples, studies that used hospitalised samples reported relatively higher prevalence of ALRTIs.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to studies that used community samples, studies that used hospitalised samples reported relatively higher prevalence of ALRTIs. For instance, 6 studies that used hospitalised samples reported prevalence above 30% [ 1 , 13 , 14 , 46 , 49 ]. See details in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation